Blanking period after radiofrequency ablation for atrial fibrillation guided by ablation lesion maturation based on serial MR imaging. (21st January 2020) - Yamashita, Kennosuke; Kwan, Eugene; Kamali, Roya; Ghafoori, Elyar; Steinberg, Benjamin A.; MacLeod, Rob S.; Dosdall, Derek J.; Ranjan, Ravi
Abstract: Background: Recent guidelines recommend a 3‐month blanking period after atrial fibrillation (AF) ablations, which are based on clinical observation. Our goal was to quantify the timeline of the radiofrequency ablation lesion maturation using serial late gadolinium enhancement‐magnetic resonance imaging (LGE‐MRI) and to develop a blanking period estimate based on visible lesion maturation. Methods: Inclusion criteria targeted patients who underwent AF ablation and at least four MRI scans: at baseline before ablation, within 24 hours after (acute), between 24 hours and 90 days after (subacute), and more than 90 days after ablation (chronic). Central nonenhanced (NE) and surrounding hyperenhanced (HE) area volumes were measured and normalized to chronic lesion volume. Results: This study assessed 75 patients with 309 MRIs. The acute lesion was heterogeneous with a HE region surrounding a central NE region in LGE‐MRI; the acute volume of the total (HE + NE) lesion was 2.62 ± 0.46 times larger than that of the chronic lesion. Acute T2‐weighted imaging also showed a relatively large area of edema. Both NE and HE areas gradually receded over time and NE was not observed after 30 days. Larger initial NE volume was associated with a significantly greater chronic scar volume and this total lesion volume receded to equal the chronic lesion size at approximately 72.5 days (95% prediction interval: 57.4‐92.2). Conclusion: On the basis of serial MRI, atrial ablation lesions are often fully mature before the typical 90‐day blanking period, which could support more timely clinical decision making for arrhythmia recurrence.